A amplitude dos efeitos das decisões sobre questão constitucional de repercussão geral : critérios para aplicação de precedentes no direito brasileiro - Ferraz, Taís Schilling (2015)
This dissertation analyzes the implementation of the general repercussion on the legal framework of extraordinary appeals and the impact of the decisions delivered by the Supreme Court on the corresponding constitutional issues. This work studies the origins of the institute, in order to understand what has motivated the introduction of a precedent respecting system in Brazilian law. Identifies the difficulties, the resistances and risks on transposing mechanisms forged in the legal culture of the common law, to a dogmatic paradigm, which gives to statute law, with its generality and abstraction, the role of being the gravitational center of the entire legal system. Investigates the phenomena of objectification on constitutionality diffuse control and the abstraction of the constitutional issue from extraordinary appeals. Compares the developing system in Brazil with the common law model, warning for the differences in the precedent generation in either system, and for the difficulties involving the subsequent ratio decidendi extraction from a general repercussion precedent, formed with conviction elements located far beyond the case individually elected as a paradigm. It argues that in the new system, the function of carrying out justice is reserved to originary judicial organs while is reserved for the Supreme Court the role of being a Constitutional Court. Defending the importance on acknowleging in Supreme Court decision authentic sources of law, the study recognizes the changing potential on establishing a precedent respecting system in Brazil. Alerts, however, to the risk of throwback, in case of not noticing the biases which whom the entire legal community is historically conditioned, the peculiarities of local precedents, and the tendency to adopt a syllogistic-deductive structure of decision, in which such precedents could start to occupy the same role already reserved for the law, in its generality and abstraction.